Synthesis of dyes derived from 1-aryl-5-amino-4-cyanopyrazoles - Gupta, Sanjay (2007)
Eight dyes were prepared by diazotisation of substituted amino-cyano pyrazoles and coupling to anilines or 2-naphthol. The dyes were fully characterised by spectroscopic techniques. The cyano group of the pyrazoles was found to be susceptible to hydrolysis during preparation.